Some related criminological aspects with Intentional Homicides in Costa Rica - Sáenz Rojas, Mario Alberto (2022)
This article presents some psychosocial and juridical aspects of voluntarymanslaughters that occurred in Costa Rica during the 1998-1999 period. The study isbased on guilty verdicts given by the justice courts. The outcomes indicate that thereare no significant differences between manslaughter and murder; fire weapons werethe main way for committing murder; nearly one in four offenders had a criminalrecord, and in two thirds of the cases, the victim and the offender knew each other.